2021
DOI: 10.1128/jcm.03004-20
|View full text |Cite
|
Sign up to set email alerts
|

Portable RT-PCR System: a Rapid and Scalable Diagnostic Tool for COVID-19 Testing

Abstract: Combating the ongoing coronavirus disease 2019 (COVID-19) pandemic demands accurate, rapid, and point-of-care testing with fast results to triage cases for isolation and treatment. The current testing relies on RT-PCR, which is routinely performed in well-equipped laboratories by trained professionals at specific locations. However, during busy periods high numbers of samples queued for testing can delay the test results, impacting upon efforts to reduce the infection risk. Besides, the absence of well-establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Despite these drawbacks, RT-PCR is still the gold standard for verifying COVID-19 diagnosis. Since the outbreak of the pandemic, numerous efforts have been made to produce handheld PCR devices [56,57]. CovidNudge, a lab-on-a-chip device, can conduct sample preparation and real-time RT-PCR in remote locations.…”
Section: Real-time Pcr (Qpcr) As a Reference Testmentioning
confidence: 99%
“…Despite these drawbacks, RT-PCR is still the gold standard for verifying COVID-19 diagnosis. Since the outbreak of the pandemic, numerous efforts have been made to produce handheld PCR devices [56,57]. CovidNudge, a lab-on-a-chip device, can conduct sample preparation and real-time RT-PCR in remote locations.…”
Section: Real-time Pcr (Qpcr) As a Reference Testmentioning
confidence: 99%
“…The successful use of the Biomeme PCR machine as portable PCR apparatus for the rapid testing of COVID-19 was also documented in the work of Zowawi et al 29 Other previous works have shown the successful design and development of portable PCR techniques, such as RT-PCR-assisted lab-ona chip-based optical detection, 30 portable rotary real-time ī„„uorescent PCR, 31 a miniaturized PCR-based portable bioaerosol, 32 and others. These breakthroughs pave a path for the future development of miniaturized PCR-based electrochemical biosensors, which have the potential to revolutionize healthcare, particularly in dengue diagnostics.…”
Section: Introductionmentioning
confidence: 89%
“…If a space does not exist for an isobox, then even a well-ventilated room inside the built structure or a well signaled tent outside could be the solution for small healthcare facilities. Additionally, in the triage area, a uni-directional flow of patients in one-way in and one-way out, an emergency isolation pathway for critically ill patients, available COVID-19 testing for early evaluation in ER area, and a secured connection into an intensive care unit (ICU) or advanced healthcare care and resources, should be obtained [ 3 , 4 ]. Dedicated clinical staff should be assigned for the evaluation of patients presenting with COVID-19 symptoms at triage.…”
Section: Triage Of Suspected Covid-19 Patientsmentioning
confidence: 99%
“…A limited number of family members and caregivers can accompany patients who need assistance and must always be in accordance with COVID-19 national guidelines and local protocols. Each healthcare facility should follow previously agreed local or regional preventive protocols against contamination of COVID-19 in the ED, including screening for COVID-19 among triage patients [ 4 , 10 ].…”
Section: Triage Of Suspected Covid-19 Patientsmentioning
confidence: 99%